Intrauterine Growth Curves for Singleton Live Babies in Paropakar Maternity and Women’s Hospital in Nepal - Aryal, D R; Gurung, R; Misra, S; Khanal, P; Pradhan, A; Gurubacharya, S M (Journal of Nepal Health Research Council, 2012)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]–><!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]–> Background: To construct birth weight, crown heel length and head circumference centile chart referenced to gestational age for Nepalese infants. Methods: The study was conducted over a period of six months. It included consecutive live births from 28 to 42 weeks of gestation. Their birth weight, crown-heel length and head circumference were recorded. Smoothed percentile values along with curves were created using the Lambda Mu Sigma (LMS) method. The curves were compared with one of the Indian study. Results: A total of 9710 newborns were measured. The mean birth weight, crown-heel length, head circumference at 40 weeks were 3023g, 49.22cm and 33.61cm respectively. Smoothed percentile values calculated gave the cutoffs for defining small and large gestational age for Nepalese newborns. Comparison with Indian study showed significant difference (p<0.01) in weight. The Indian babies weighed less than Nepalese babies. Conclusions: The referenced growth standards help in clinical assessment, defining and identifying high risk newborns, thus, leading to improved care and management of neonates. It should help public health policy makers to track population difference due to several factors, intervene and find response over time. <span style="font-size: 12.0pt; line-height: 115%; font-family: ";Times New Roman";,";serif";; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">Â Keywords: centile, crown-heel length, gestation, growth curves, head circumference, newborn and weight.<!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>